Institutional Partnership Model of Cassava Sustainable Agribusiness in Lampung Province - Zulkarnain Zulkarnain; Wan Abbas Zakaria; Dwi Haryono; Ktut Murniati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2021)
The research objective was to analyze a partnership institutional model that ensures the sustainability of cassava agribusiness in Lampung Province. The research was conducted in Central Lampung District using a case study at PT. ABC and survey methods to 131 cassava farmers taken purposively. The analysis used is descriptive qualitative. The result of this research is that the sustainable cassava agribusiness partnership institution was carried out in horizontal coordination between the cassava farmer institution and the tapioca factory so that the problems of farmers and factories can be resolved such as good selling price of cassava and continuous factory capacity.